Uncertainty dynamics in energy planning models: An autoregressive and Markov chain modeling approach - Guevara, Esnil; Babonneau, Frédéric; Homem-de-Mello, Tito (Computers & industrial engineering, 2024)
This paper deals with the modeling of stochastic processes in long-term multi-stage energy planning problems when limited information is available about the distributions of such processes. Starting from simple estimates of variation intervals for uncertain parameters, such as energy demands and costs, we model the temporal correlation of these parameters through carefully constructed autoregressive (AR) models that respect the intervals defined in each period. We introduce a coefficient for “zigzag” effects in the evolution of uncertain processes, which controls the correlation across periods and also the likelihood of extreme scenarios. To preserve the convexity of the stochastic problem, we discretize the AR models associated with the cost parameters involved in the objective function by Markov chains. The resulting formulation is then solved using a Stochastic Dual Dynamic Programming (SDDP) algorithm available in the literature that handles finite-state Markov chains. Our numerical experiments, carried out on the Swiss energy system, show a very desirable adaptation strategy of investment decisions to uncertainty scenarios, a behavior that is not observed when the temporal correlation is ignored. Moreover, the solutions lead to better out-of-sample cost performances, especially on extreme scenario realizations, than the non-correlated ones which usually result in overcapacities to protect against high, but unlikely, parameter variations over time. •We model temporal uncertainty correlations with AR models from simple ranges.•We introduce a coefficient that controls temporal correlation and extreme scenarios.•To preserve convexity, we discretize the AR models by Markov chains.•The stochastic formulation is then solved with a SDDP algorithm.•Experiments show a desirable adaptation of investments and better out-of-sample costs.